Risk factors and clinical significance of refractory pain in patients with bone metastases: a comprehensive meta-analysis - Li, Qiju; Liu, Qingqing; Yang, Liu; Li, Qin; Zhang, Aimin (Frontiers in Neurology, 2025)
BackgroundRefractory cancer pain, especially bone pain, presents a major clinical challenge that is difficult to manage despite the use of multimodal analgesic strategies. This meta-analysis aims to estimate the prevalence of refractory cancer pain in this patient population and to identify potential predictors that may increase the likelihood of developing such pain. In addition, we performed a systematic review of previous studies that delve into more effective pain strategies.MethodsThis meta-analysis and systematic review were conducted in accordance with the PRISMA guidelines. A comprehensive search was performed using PubMed, Web of Science, Embase, and the Cochrane Library on risk factors for refractory metastatic bone pain. The inclusion criteria focused on studies reporting the incidence and/or risk factors associated with refractory cancer pain, providing relevant statistical measures such as odds ratios (OR), hazard ratios (HR), or relative risks (RR). The methodological quality of the studies was assessed using the Newcastle–Ottawa Scale (NOS), and a random-effects meta-analysis was conducted using the R programming language.ResultsThe present study included eight studies with a cumulative sample size of 2,774 patients. The aggregated incidence of refractory cancer pain was found to be 70% [95% confidence interval (CI): 42 to 88%] using a random-effects model, highlighting a significant prevalence of pain that remains unresponsive to treatment. Notably, the heterogeneity among the included studies was considerable (I2 = 98%, τ2 = 2.7198). The analysis also identified several critical predictors of refractory cancer pain. The presence of multiple bone metastases was consistently linked to an increased likelihood of refractory cancer pain with an OR of 3.94 (95% CI: 2.64–5.87). Similarly, lytic bone metastases demonstrated a high OR of 5.99 (95% CI: 3.17–11.30). Furthermore, there was a strong correlation between the occurrence of refractory cancer pain with severe acute pain (OR = 219.20, 95% CI: 0.26–188127.63), breakthrough pain (OR = 16.44, 95% CI: 0.60–448.07), and psychological comorbidities such as depression (OR = 3.91, 95% CI: 1.22–2048.64) and anxiety (OR = 4.22, 95% CI: 1.22–2048.64).ConclusionRefractory cancer pain, observed in approximately 70% of patients with bone metastases, poses a significant clinical challenge. Refractory cancer pain predictors include the presence of multiple and lytic bone metastases, severe acute pain, breakthrough pain, and psychological comorbidities. Collectively, our findings highlight the need for improved pain management strategies that address both the physical and psychological aspects of cancer pain.